Mood and Emotional Changes After PEERS® Program in Parents of Young Adults With Autism Spectrum Disorder - Son, Chansoo; Yoo, Hee Jeong; Kim, Joo-Hyun; Oh, Miae (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2023)
This study examined the changes in anxiety and depressive symptoms in the parents of Korean adults with autism spectrum disorder (ASD) after participating in the Korean version of the Program for the Education and Enrichment of Relational Skills for Young Adults (PEERS -YA-K). Forty-six parents were enrolled (mean age 54.7 years; 22 fathers and 24 mothers), of whom 27 participated in the PEERS - YA-K as social coaches. Participants completed self-report scales, including the Test of Young Adult Social Skills Knowledge (TYASSK), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Symptom Check-List-90-R (SCL-90-R). The scales were administered three times: before and after the 16-week program and 4 months after the program ended. Differences between participant variables at pretreatment, post-treatment, and follow-up were analyzed using paired-sample t-tests. Participants showed a significant improvement in their social skills knowledge (TYASSK) (p<0.01). There was a significant improvement in the BAI and BDI scores of parents with severe depressive and anxiety symptoms at the baseline (p<0.05). Paternal paranoia and maternal hostility results also significantly improved on the SCL-90-R. This study suggests that PEERS -YA-K can reduce parental anxiety and depressive symptoms. To the best of our knowledge, this is the first to compare the degree of depression and anxiety after PEERS -YA-K in parents of adults with ASD.